Methodology and optimization tool for a personalized low environmental impact and healthful diet specific to country and season. (4th May 2021) - Walker, Christie; Pfister, Stephan; Hellweg, Stefanie
Abstract: To remain within the limits of the planetary boundaries and address increasing disease rates due to poor eating habits, there needs to be a major shift in dietary patterns. The composition of an optimal diet changes depending on location, season, and personalized dietary needs. We develop a methodology to build a 500+ food item, nutrient, and environmental impact database specific to a given country and month, which includes several life cycle stages of a food item and calculates impacts depending on from where the item is sourced. This database is then used to develop a detailed and personalized, healthful, low impact diet by using linear optimization. We applied this methodology to several case studies to compare what low impact diets would look like depending on country (Switzerland vs. Spain), season (August vs. February), sex, the inclusion of dietary supplements, and for different diet types and impact categories (climate change and biodiversity loss). Results indicate that, although optimized diets are similar, there are marked differences in the detailed composition depending on country, season, and impact considered, especially regarding legume choice. The lowest impact diet contained local and imported foods as well as fish. Vegan diets had the lowest impact only when incorporating a supplement to meet nutrient needs. We developed a tool to be used for personalized diet composition assessments for any global geographical location and season. We anticipate this work to be useful for developing country‐ and season‐specific dietary guidelines and for consumers hoping to reduce their own personal impacts.